(untitled) (Fiep Bulletin - online, 2014)
Marijuana is the drug most used in the world and in the Brazil, where 19,4% of Brazilian they already made use drug in the life, what contrasts enough with the numbers of the EUA (38,9%). The marijuana is derived of the plant Cannabis Sativa and has in their composition more than 400 substances, being 60 canabinnóids and the main active representative is delta- 9-tetrahidrocanabinol (THC). It could be smoked or ingested, and in the first the effects are faster, so the second the absorption tax is larger. The effect that her causes in the user is of palpitation, elevation of the blood pressure (BP), hypotension orthostatic and hypertension when seating or lying. All those situation can take the user to have an acute infarct of the myocardium. The muscular activity also causes changes physiologic during the execution, that are similar to caused them by the marijuana. And that it can take to a cardiovascular load that will unchain an infarct of the myocardium.